Penyuluhan Terintegrasi TikTok Affiliate, Manajemen Keuangan, dan NPWP bagi Peningkatan Kapasitas Usaha Pelaku UMKM di Kelurahan Temberan, Pangkalpinang - Nana Adriana; M. Ilham Wira Pratama; Rifa Umaimah; Arita Arita; Nada Alesandro; Aldila Ramrada (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2026)
MSMEs in Temberan Village, Pangkalpinang City, face limitations in digital marketing, financial management, and tax administration. An initial assessment of 32 participants showed that 84.4% had not utilized social-media commerce features, 78.1% still mixed personal and business finances, 71.9% kept no financial records, and 75.0% did not have a Taxpayer Identification Number (NPWP). This community engagement program aimed to strengthen MSME capacity through digital marketing, simple financial management, and tax administration. Conducted from June to July 2026, the program employed a Participatory Action Research (PAR) approach through five phases: participatory mapping, joint planning, action implementation, practice mentoring, and reflection and evaluation. Evaluation focused on changes in participants' knowledge and practices. The aggregate mean knowledge score increased from 38.8 to 78.7, with an N-Gain of 0.65 (moderate category). At the practice level, 78.1% of participants were able to utilize digital marketing channels and prepare promotional content drafts, 65.6% were able to maintain cash-flow records while separating personal and business transactions, and 17 of 24 participants (70.8%) who initially had no NPWP completed the registration process. Five of the six program indicators were achieved. The main finding revealed a knowledge–practice gap in financial management: this area recorded the highest N-Gain (0.71) but the lowest practical achievement because some participants' business transactions remained intertwined with household needs. Program sustainability was supported through six peer facilitators, simple financial-recording tools, institutional support from the Family Welfare Empowerment (PKK) group, and follow-up consultation. These results highlight the importance of practice-based mentoring in translating increased capacity into more independent and sustainable business-management practices.